2017
DOI: 10.1186/s12906-017-1676-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperthermic baths on depression, sleep and heart rate variability in patients with depressive disorder: a randomized clinical pilot trial

Abstract: BackgroundDespite advances in the treatment of depression, one-third of depressed patients fail to respond to conventional antidepressant medication. There is a need for more effective treatments with fewer side effects. The primary aim of this study was to determine whether hyperthermic baths reduce depressive symptoms in adults with depressive disorder.MethodsRandomized, two-arm placebo-controlled, 8-week pilot trial. Medically stable outpatients with confirmed depressive disorder (ICD-10: F32/F33) who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 37 publications
3
31
0
3
Order By: Relevance
“…[33] This pilot study suggests that hyperthermic baths do have generalized efficacy in depressed patients. In another study the spa therapy shows a potential approach for breast cancer rehabilitation.…”
Section: Known As Balneotherapymentioning
confidence: 85%
“…[33] This pilot study suggests that hyperthermic baths do have generalized efficacy in depressed patients. In another study the spa therapy shows a potential approach for breast cancer rehabilitation.…”
Section: Known As Balneotherapymentioning
confidence: 85%
“…Fever, respectively hyperthermia, has been used as a medical treatment since ancient times, and beneficial effects of fever on mental illness were already described in antiquity (10). Based on recent findings, there is growing scientific evidence that hyperthermic baths (HTB) and whole body hyperthermia (WBH) might be efficacious for treatment of depressive disorders (11)(12)(13)(14). The results of a non-controlled HTB study with 20 depressive patients showed an improvement in the 21-item Hamilton Depression Rating Scale (15) after five baths (11).…”
Section: Introductionmentioning
confidence: 99%
“…Coordination among different specific treatment registries that already exist (e.g., the vagal nerve stimulation registry that the FDA requires(Aaronson et al, 2017;Naumann et al, 2017) and the transcranial magnetic stimulation registry recently launched by Neurostar (NeuroStar Advanced Therapy, 2017) and that have been suggested (e.g., a ketamine registry; Singh, Singh, Kar, & Pahuja, 2017) would be a necessary step. Documenting all steps in such investigations, reporting on all planned outcomes, and otherwise ensuring complete transparency for this study are critical actions in adding to the professional literature.…”
mentioning
confidence: 99%
“…For instance, a treatment registry using common data elements could substantially help clarify the criteria that best define TRD, what the course of illness is, and how interventions might affect that course. Coordination among different specific treatment registries that already exist (e.g., the vagal nerve stimulation registry that the FDA requires(Aaronson et al, 2017;Naumann et al, 2017) and the transcranial magnetic stimulation registry recently launched by Neurostar (NeuroStar Advanced Therapy, 2017) and that have been suggested (e.g., a ketamine registry;Singh, Singh, Kar, & Pahuja, 2017) would be a necessary step. Data quality is a key challenge for such an enterprise.…”
mentioning
confidence: 99%